Determining optimal clinical target volume margins based on microscopic tumor extension in patients with non-small-cell lung cancer undergoing chemotherapy or chemotherapy combined with immunotherapy - Zhang, Yujiao; Song, Xiao; Li, Jiaran; Zhao, Fen; Li, Li; Liu, Ning; Zhao, Miaoqing; Yuan, Shuanghu (Frontiers in Oncology, 2026)
BackgroundThere is currently no unified understanding of the clinical target volume (CTV) margins for radiotherapy in non-small cell lung cancer (NSCLC), after chemotherapy or chemotherapy combined with immunotherapy. This study aimed to explore margins around the gross tumor volume (GTV) to infer the CTV in NSCLC, after chemotherapy or chemotherapy combined with immunotherapy, using microscopic tumor extension (ME).MethodsWe retrospectively analyzed 185 patients with stage II and III NSCLC who underwent surgery without neoadjuvant therapy or with neoadjuvant chemotherapy or chemotherapy combined with immunotherapy. We assessed the correlation between the radiological (last preoperative computed tomography image) and pathological (postoperative gross specimens) tumor size, measured the distance of ME under a digital microscope, and determined the correlation between clinicopathological characteristics and ME.ResultsFor the same tumor sample, a significant correlation was observed between the radiological and macroscopic sizes (r=0.836). With a 5% error risk, we applied a margin of 6.80 mm and 6.00 mm to the adenocarcinoma (ADC) and squamous cell carcinoma (SCC) of direct surgery, respectively; a margin of 5.20 mm and 4.20 mm, to the ADC and SCC receiving chemotherapy, respectively; and a margin of 4.60 mm and 1.20 mm to the ADC and SCC receiving chemotherapy combined with immunotherapy, respectively. The ME value of a tumor correlated with the pathological type, tumor stage, and preoperative treatment methods.ConclusionsDifferent CTV margins should be adopted for patients with NSCLC who are receiving different treatments.